Nasal challenges: managing metallic foreign bodies: a case series - Thakkar, Himanshu (International Journal of Contemporary Pediatrics, 2025)
Foreign bodies within the external nose, though uncommon, pose potential risks including chronic inflammation and localized infection, despite the inert nature of most metallic materials. Prompt identification and appropriate removal are essential to mitigate complications. This report presents three clinical cases involving embedded nasal foreign bodies, each successfully diagnosed via endoscopic examination and managed through an open rhinoplasty approach. The open rhinoplasty technique offers a distinct advantage by ensuring optimal surgical exposure while preserving aesthetic outcomes, surpassing the cosmetic limitations associated with conventional incisions. Although literature on nasal foreign bodies remains limited-often focusing on durations ranging from three months to five years—these cases underscore the importance of early and precise diagnosis. Radiographic evaluation, particularly with computed tomography (CT), remains the gold standard for accurate localization of intranasal foreign bodies. Upon confirmation, surgical extraction is typically warranted, with endoscopic-assisted methods increasingly favored for their minimally invasive nature and lower procedural risk. In asymptomatic individuals, conservative management with regular radiographic monitoring may be considered as an alternative to immediate intervention.